Mengkaji Ulang Living Qur’an: Tren Studi Al-Qur’an dan Dinamikanya - Nasir Iqbal (Khulasah : Islamic Studies Journal, 2026)
Living Qur’an (LQ) studies have shown an increasingly massive development within Qur’anic studies in Indonesian Islamic higher education, particularly since the strengthening of social, cultural, and empirical approaches to understanding Muslim religious practices. This article aims to revisit the Living Qur’an by highlighting the tension between phenomenological tendencies and the need for a more reflective theoretical foundation. This study employs a qualitative method based on library research, utilizing a phenomenology of religion approach alongside a historical-chronological analysis of the development of the Living Qur’an discourse in Indonesia. The results of the study indicate that the Living Qur’an emerged as a response to the dominance of normative-textual Qur’anic studies, as well as an effort to read the Qur’an within the context of social reception and praxis in Muslim societies. The appeal of this study lies in its ability to uncover the process of internalizing Qur’anic values into local cultures and long-standing living religious traditions. However, the rapid production of Living Qur’an research also reveals a weak methodological footing, causing many studies to stop at descriptive phenomenology without adequate critical analysis. This article asserts the necessity of a conceptual reconstruction of the Living Qur’an as a phenomenological-receptive study accompanied by theoretical awareness, enabling it to contribute substantively to the development of contextual, reflective, and sustainable Qur’anic studies.